Answer

Verified

406.5k+ views

**Hint:**Use the conversion: - \[\sec x=\dfrac{1}{\cos x}\] and simplify the given function. Now, rationalize the denominator by multiplying and dividing the obtained function with \[\left( 1-\cos x \right)\]. Use the identity: - \[{{\cos }^{2}}x+{{\sin }^{2}}x=1\] to simplify the denominator. Now, break the terms and write the function as: - \[\int{\csc x\cot x dx}-\int{{{\cot }^{2}}xdx}\] and use the identity \[{{\cot }^{2}}x+1={{\csc }^{2}}x\], for further simplification. Finally, use the formulas: - \[\int{\csc x\cot x dx}=-\csc x\] and \[\int{{{\csc }^{2}}xdx}=-\cot x\] to get the answer. Add the constant of indefinite integration ‘c’ to complete the integral.

**Complete step-by-step solution:**

Here, we have been provided with the function \[\dfrac{1}{1+\sec x}\] and we are asked to determine its integral, that means we have to integrate this function.

Now, let us assume the required integral as ‘I’. So, we have,

\[\Rightarrow I=\int{\dfrac{1}{1+\sec x}dx}\]

Using the conversion: - \[\sec x=\dfrac{1}{\cos x}\], we get,

\[\begin{align}

& \Rightarrow I=\int{\left( \dfrac{1}{1+\dfrac{1}{\cos x}} \right)dx} \\

& \Rightarrow I=\int{\dfrac{\cos x}{1+\cos x}dx} \\

\end{align}\]

Rationalizing the denominator by multiplying and dividing the function with \[\left( 1-\cos x \right)\], we get,

\[\Rightarrow I=\int{\dfrac{\cos x\left( 1-\cos x \right)}{\left( 1+\cos x \right)\left( 1-\cos x \right)}dx}\]

Using the algebraic identity: - \[\left( a+b \right)\left( a-b \right)={{a}^{2}}-{{b}^{2}}\], we get,

\[\Rightarrow I=\int{\left[ \dfrac{\cos x-{{\cos }^{2}}x}{\left( 1-{{\cos }^{2}}x \right)} \right]dx}\]

We know that, \[{{\cos }^{2}}x+{{\sin }^{2}}x=1\], so we have \[\left( 1-{{\cos }^{2}}x \right)={{\sin }^{2}}x\]. Therefore, the integral ‘I’ becomes: -

\[\Rightarrow I=\int{\left( \dfrac{\cos x-{{\cos }^{2}}x}{{{\sin }^{2}}x} \right)dx}\]

Breaking the integral terms, we get,

\[\Rightarrow I=\int{\dfrac{\cos x}{{{\sin }^{2}}x}dx}-\int{\dfrac{{{\cos }^{2}}x}{{{\sin }^{2}}x}dx}\]

The above expression can be simplified as: -

\[\begin{align}

& \Rightarrow I=\int{\dfrac{\cos x}{\sin x}\times \dfrac{1}{\sin x}dx}-\int{{{\left( \dfrac{\cos x}{\sin x} \right)}^{2}}dx} \\

& \Rightarrow I=\int{\cot x\csc xdx}-\int{{{\cot }^{2}}xdx} \\

\end{align}\]

We know that: - \[{{\cot }^{2}}x+1={{\csc }^{2}}x\], so we have \[{{\cot }^{2}}x={{\csc }^{2}}x-1\]. Replacing the value of second part of the above integral, we get,

\[\begin{align}

& \Rightarrow I=\int{\cot x\csc xdx}-\int{\left( {{\csc }^{2}}x-1 \right)dx} \\

& \Rightarrow I=\int{\cot x\csc xdx}-\int{{{\csc }^{2}}xdx}+\int{dx} \\

\end{align}\]

Using the basic formulas: - \[\int{\csc x\cot xdx}=-\csc x\] and \[\int{{{\csc }^{2}}xdx}=-\cot x\], we get,

\[\begin{align}

& \Rightarrow I=-\csc x-\left( -\cot x \right)+x \\

& \Rightarrow I=x+\cot x-\csc x \\

\end{align}\]

Since, the required integral was an indefinite integral, so we add a constant of indefinite integration ‘c’ at the end. So, we have,

**\[\Rightarrow I=x+\cot x-\csc x+c\], where ‘c’ = constant of integration.**

**Note:**One may note that we can also solve the question by using a different approach. What we can do is after using the conversion: - \[\sec x=\dfrac{1}{\cos x}\] we will apply the half angle formula given as: - \[\cos x=\dfrac{1-{{\tan }^{2}}\dfrac{x}{2}}{1+{{\tan }^{2}}\dfrac{x}{2}}\]. Then in the numerator we will use the identity \[1+{{\tan }^{2}}\dfrac{x}{2}={{\sec }^{2}}\dfrac{x}{2}\] for the simplification. In the next step we will substitute \[\tan \left( \dfrac{x}{2} \right)=k\] and \[{{\sec }^{2}}\dfrac{x}{2}dx=2dk\]. In this case the obtained integral will be \[x-\tan \dfrac{x}{2}\]. Actually, we you will simplify \[\cot x-\csc x\] using the formulas: - \[1-\cos \theta =2{{\sin }^{2}}\dfrac{\theta }{2}\] and \[\sin \theta =2\sin \dfrac{\theta }{2}\cos \dfrac{\theta }{2}\], you will get \[\left( -\tan \dfrac{x}{2} \right)\], so you can conclude that the answer we have obtained is correct and only the form is different. Do not forget to add the constant of indefinite integration ‘c’ in the end otherwise the answer would be considered incomplete.

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Mark and label the given geoinformation on the outline class 11 social science CBSE

When people say No pun intended what does that mea class 8 english CBSE

Name the states which share their boundary with Indias class 9 social science CBSE

Give an account of the Northern Plains of India class 9 social science CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Trending doubts

Which are the Top 10 Largest Countries of the World?

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

How do you graph the function fx 4x class 9 maths CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Why is there a time difference of about 5 hours between class 10 social science CBSE